2015
DOI: 10.1002/ajmg.b.32331
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying naturalistic social gaze in fragile X syndrome using a novel eye tracking paradigm

Abstract: A hallmark behavioral feature of fragile X syndrome (FXS) is the propensity for individuals with the syndrome to exhibit significant impairments in social gaze during interactions with others. However, previous studies employing eye tracking methodology to investigate this phenomenon have been limited to presenting static photographs or videos of social interactions rather than employing a real-life social partner. To improve upon previous studies, we used a customized eye tracking configuration to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 47 publications
2
33
1
Order By: Relevance
“…Interestingly, using eye gaze shifts—eye gaze to a person’s face that alternates between the person and an object—for the purposes of behavior requests, joint attention, and responding to communication has been reported as relatively intact in infants and young children with FXS (Marschik et al, 2014; Roberts et al, 2002). These findings contrast with research on older children, adolescents, and adults that has identified difficulties using eye gaze for initiating and maintaining social interactions (Hall et al, 2015; Williams, Porter, & Langdon, 2013) and gaze avoidance, (Cohen et al, 1988; Murphy, Abbeduto, Schroeder, & Serlin, 2007) as core aspects of the FXS phenotype. However, these studies have primarily focused on eye gaze in FXS outside of a communication context.…”
Section: Introductioncontrasting
confidence: 95%
“…Interestingly, using eye gaze shifts—eye gaze to a person’s face that alternates between the person and an object—for the purposes of behavior requests, joint attention, and responding to communication has been reported as relatively intact in infants and young children with FXS (Marschik et al, 2014; Roberts et al, 2002). These findings contrast with research on older children, adolescents, and adults that has identified difficulties using eye gaze for initiating and maintaining social interactions (Hall et al, 2015; Williams, Porter, & Langdon, 2013) and gaze avoidance, (Cohen et al, 1988; Murphy, Abbeduto, Schroeder, & Serlin, 2007) as core aspects of the FXS phenotype. However, these studies have primarily focused on eye gaze in FXS outside of a communication context.…”
Section: Introductioncontrasting
confidence: 95%
“…The Working Group stated that measures of social cognition have not been well studied in FXS. It was noted that the relationship between performance on such measures and actual social behavior is not strong [77]. The Working Group concluded that both the Social Responsiveness Scale (SRS) [78] and the use of eye-tracking technology to assess attention to social events were promising but required further validation in FXS.

Social Responsiveness Scale (SRS).

…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…Similarly, observational studies of young children with FXS suggest that joint attention and joint engagement are commensurate with developmental level (Hahn et al, 2016; Roberts et al, 2002). Also during social interactions, it seems that young children with FXS are particularly skilled at using eye gaze shifts for the purpose of sharing interests, making requests, and commenting (Roberts et al, 2002), despite the extant research on children, adolescents, and adults with FXS that reports impairments in eye gaze, especially for social purposes (Cohen et al, 1988; Hall et al, 2015; Hessl, Glaser, Dyer-Friedman, & Reiss, 2006; Murphy et al, 2007; Wolff et al, 1989). Thus, it is possible that difficulties with eye gaze have not yet emerged as a phenotypic behavior in very young children with FXS (Marschik et al, 2014; Wolff et al, 1989) and may actually be a key behavior that supports joint attention in early development.…”
Section: Early Social Development In Neurogenetic Disordersmentioning
confidence: 99%